Electronic evidence and technology-assisted review - Almquist, Brian (My University, 2019)
We consider the technological developments relevant to procedures characterized as “discovery” in legal proceedings over the last two decades. As storage technology has improved, the idea of a “document” as a piece of discrete discoverable information is becoming increasingly outdated. The courts, while adapting to the new technologies, have also had to reckon with increasing costs of document production, and more expensively, review of information for relevance and privilege or work-product protections. Technology-Assisted Review, using machine learning, is rapidly being employed to handle large document productions. This brings eDiscovery right in line with some of the most interesting current developments in information technology.
Keywords: electronically stored information; electronic discovery; technology-assisted review; information governance